2020
DOI: 10.1021/acs.jafc.9b05912
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Bioaccessibility of Iodine in Food Prepared from Agronomically Biofortified Wheat and Rice and Impact of Cofertilization with Zinc and Selenium

Abstract: Enrichment of food crops with iodine is an option to alleviate dietary deficiencies. Therefore, foliar iodine fertilizer was applied on wheat and rice, in the presence and absence of the other micronutrients zinc and selenium. This treatment increased the concentration of iodine, as well as zinc and selenium, in the staple grains. Subsequently, potential iodine losses during preparation of foodstuffs with the enriched grains were studied. Oven-heating did not affect the iodine content in bread. Extraction of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 51 publications
(107 reference statements)
2
33
0
2
Order By: Relevance
“…Thus, a successful adoption of this agronomic strategy at least in the five major rice producing countries would contribute significantly to the daily micronutrient intake and alleviation of micronutrient malnutrition. Very recent studies using a simulated human digestive system showed that Zn, I and Se in agronomically biofortified foods are sufficiently bioaccessible for use by the human body (Cakmak et al, 2020). In a further human Zn absorption study conducted at ETH-Zurich, agronomically biofortified wheat with Zn made a significant contribution to the dietary Zn absorption in humans (Signorell et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a successful adoption of this agronomic strategy at least in the five major rice producing countries would contribute significantly to the daily micronutrient intake and alleviation of micronutrient malnutrition. Very recent studies using a simulated human digestive system showed that Zn, I and Se in agronomically biofortified foods are sufficiently bioaccessible for use by the human body (Cakmak et al, 2020). In a further human Zn absorption study conducted at ETH-Zurich, agronomically biofortified wheat with Zn made a significant contribution to the dietary Zn absorption in humans (Signorell et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…3, are influenced by several variables such as method of Se supplementation, Se dose and species, soil Se, cropping systems and tillage practices, environmental and weathering conditions, crop species/variety, plant growth stage and joint application with other micronutrients (Bañuelos et al 2017;D'Amato et al 2020;Dall'Acqua et al 2019;Hawrylak-Nowak, 2013;Schiavon et al 2013Schiavon et al , 2016. So far, most research dealing with Se biofortification has targeted at the application of Se alone or occasionally combined with only one micronutrient, generally silicon, iodine (I) or zinc (Zn) (Golubkina et al 2018;Sattar et al 2017;Cakmak et al 2020;Golob et al 2020). Only few studies have addressed crop biofortification with multiple micronutrients (Mao et al 2014;Zou et al 2019), although deficiency of multiple trace nutrients is an issue of global concern.…”
Section: How Can Crops Be Enriched With Selenium? Conventional and Nomentioning
confidence: 99%
“…Another subject of research was the impact of I on oxyreduction, e.g., in lettuce (Blasco et al, 2008;Dávila-Rangel et al, 2020), the process of photosynthesis in kohlrabi (Golob et al, 2020) and basil (Kiferle et al, 2019), nitrate (V) content in four Brassica genotypes (Gonnella et al, 2019), and changes in the content of macro-and microelements in green bean and lettuce (Dobosy et al, 2020). Furthermore, there was also research devoted to the efficacy of I − and/or IO 3 − uptake by plants, depending on the additional application of other elements, such as selenium in kohlrabi (Golob et al, 2020), zinc, selenium, and iron in wheat (Zou et al, 2019), and zinc and selenium in wheat and rice (Cakmak et al, 2020). The impact of I on the induction of plant resistance to diseases was also analyzed (Ajiwe et al, 2019).…”
Section: Iodine In Plantsmentioning
confidence: 99%